2009
DOI: 10.1128/jb.00158-09
|View full text |Cite
|
Sign up to set email alerts
|

GerO, a Putative Na + /H + -K + Antiporter, Is Essential for Normal Germination of Spores of the Pathogenic Bacterium Clostridium perfringens

Abstract: The genome of the pathogen Clostridium perfringens encodes two proteins, GerO and GerQ, homologous to monovalent cation transporters suggested to have roles in the germination of spores of some Bacillus species. GerO and GerQ were able to transport monovalent cations (K ؉ and/or Na ؉ ) in Escherichia coli, and gerO and gerQ were expressed only in the mother cell compartment during C. perfringens sporulation. C. perfringens spores lacking GerO were defective in germination with a rich medium, KCl, L-asparagine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…It is not surprising to see increased levels of several ion transporters in germinated spore samples considering the observation of a large efflux of cations during the early stages of germination in Bacillus species (12). Mutagenesis studies of several ion transporters have also shown that ion transport plays an important role in spore germination (10,50). It is possible that several of the identified transporters, such as the cation efflux superfamily protein CPR_0983, the cation-transporting ATPase CPR_2026, and the ion compound ABC transporter CPR_1115, serve as channels or gates for cation efflux during spore germination, especially the protein encoded by CPR_2026, which shares 47% identity with the calcium pump ATPase YloB from B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is not surprising to see increased levels of several ion transporters in germinated spore samples considering the observation of a large efflux of cations during the early stages of germination in Bacillus species (12). Mutagenesis studies of several ion transporters have also shown that ion transport plays an important role in spore germination (10,50). It is possible that several of the identified transporters, such as the cation efflux superfamily protein CPR_0983, the cation-transporting ATPase CPR_2026, and the ion compound ABC transporter CPR_1115, serve as channels or gates for cation efflux during spore germination, especially the protein encoded by CPR_2026, which shares 47% identity with the calcium pump ATPase YloB from B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known if the reduced detection is due to degradation or reduced association with the membrane during purification. It was reported previously that mutation of a putative Na ϩ / H ϩ -K ϩ antiporter, GerO (CPR_0227), containing 10 potential membrane-spanning domains, negatively affected spore germination and outgrowth (10). However, translation of GerO was observed only in the mother cell compartment and not in the forespore (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations